Metamaterial patch antenna with electromagnetic band gap (EBG) structure for WLAN application: article / Wan Mohd Jazli Azri Wan Mohd Jailani - Wan Mohd Jailani, Wan Mohd Jazli Azri (2013)
This paper presents a rectangular microstrip patch antenna with electromagnetic band gap (EBG) structures at the ground plane is applied for wireless local area network (WLAN).The antenna is designed to resonate at the 5GHz frequency. The combination of the rectangular microstrip patch antenna is fabricated on top of the substrate Rogers RO5880 with dielectric constant of 2.2 and substrate thickness is 0.508mm.Simulations and measurements have been carried out to verify the performance of EBG structures in patch antenna. All the simulation and measurement work is done by using Computer Simulation Technology (CST) software.The designsare divided into twocategories that are a conventional antenna without EBG and real antenna with EBG. Furthermore, this work is mainly focused on improving the performance of patch antenna and reducing the size of antenna by applying EBG structures. All the calculation, simulation result and measurement regarding this design also provided.